Cancer treatment and survival among cervical cancer patients living with or without HIV in South Africa - Yannick Q. Turdo; Yann Ruffieux; Tebatso M.G. Boshomane; Hannes Mouton; Katayoun Taghavi; Andreas D. Haas; Matthias Egger; Gary Maartens; Eliane Rohner (Elsevier, 2022)
Objective: To compare cancer treatment and all-cause mortality between HIV-positive and HIV-negative cervical cancer patients in South Africa. Methods: We assessed cancer treatment and all-cause mortality in HIV-positive and HIV-negative cervical cancer patients who received cancer treatment within 180 days of diagnosis using reimbursement claims data from a private medical insurance scheme in South Africa between 01/2011 and 07/2020. We assessed treatment provision using logistic regression and factors associated with all-cause mortality using Cox regression. We assigned missing values for histology and ethnicity using multiple imputation. Results: Of 483 included women, 136 (28 %) were HIV-positive at cancer diagnosis (median age: 45.7 years), and 347 (72 %) were HIV-negative (median age: 54.1 years). Among 285 patients with available ICD-O-3 morphology claims codes, the proportion with cervical adenocarcinoma was substantially lower in HIV-positive (4 %) than in HIV-negative patients (26 %). Most HIV-positive patients (67 %) were on antiretroviral therapy at cancer diagnosis. HIV-positive patients were more likely to receive radiotherapy (adjusted odds ratio [aOR] 1.90, 95 % confidence interval [CI] 1.05-3.45) or chemotherapy (aOR 2.02, 95 %CI 0.92-4.43) and less likely to undergo surgery (aOR 0.53, 95 %CI 0.31-0.90) than HIV-negative patients. HIV-positive patients were at a higher risk of death from all causes than HIV-negative patients (adjusted hazard ratio 1.52, 95 %CI 1.06-2.19). Other factors associated with higher all-cause mortality included age > 60 years and metastases at diagnosis. Conclusions: HIV-positive cervical cancer patients in South Africa had higher all-cause mortality than HIV-negative patients which could be explained by differences in tumour progression, clinical care, and HIV-specific mortality.